ABSURDITY IN THE NOVEL PERBURUAN BY PRAMOEDYA ANANTA TOER: EXISTENTIALISM STUDY - Rina Husnaini Febriyanti; Zuriyati Zuriyati; Saifurrohman Saifurrohman (Universitas Indraprasta PGRI, 2020)
Abstract: The research aims to find absurdity aspects in the main character of the novel Perburuan that was written by Pramoedya Ananta Toer. The method used was qualitative descriptive. The approach was existentialism. The research technique was done by collecting data from words, phrases, clauses, and sentences that afterwards were categorized and analysed based on absurdity aspects. By the data analysed, it was interpreted with existentialism approach. The findings of the research study displayed the absurdity aspects as follows desperation, unbelief, unafraid of anything, cynicism, soul emptiness, pseudo hope, freedom, sentimentalism, and deadness. Keywords: Absurdity; Novel of Perburuan; Existentialism.